Investment Decisions on Physical Activity Promotion: A Locality Case Study in Complex Public Health Policy Making. Issue 2 (16th April 2023) - Whitelaw, Sandy; Topping, Chris
Abstract : The role of 'best investment' methodology in shaping priorities in many health policy areas is becoming increasingly prominent. Whilst this has traditionally been seen as a technocratic exercise, the social and political context of such practices and the constructed nature of decisions are now considered significant. In this context, this article reports on a longitudinal case study of such a process that sought to identify 'best investments' in public health interventions related to promoting physical activity. Drawing on a series of conceptual resources, we describe and reflect upon the complex and invested elements that contributed to the grounded decision-making process. In conclusion we suggest the need to adopt a multifaceted and nuanced approach to resource investment decision making, including: deploying a range of appraisal assessment resources; maintaining a long-term processual perspective; involving a variety of stakeholders; accepting and embracing fallibility; and accommodating theoretical and empirical evidence-based principles.